2022
DOI: 10.3390/ijms24010103
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic Acid as a Modern Approach in Anticancer Therapy-Review

Abstract: Hyaluronic acid (HA) is a linear polysaccharide and crucial component of the extracellular matrix (ECM), maintaining tissue hydration and tension. Moreover, HA contributes to embryonic development, healing, inflammation, and cancerogenesis. This review summarizes new research on the metabolism and interactions of HA with its binding proteins, known as hyaladherins (CD44, RHAMM), revealing the molecular basis for its distinct biological function in the development of cancer. The presence of HA on the surface of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 235 publications
0
14
0
Order By: Relevance
“…HA turnover occurs in various molecular weights of HA distinguished by their polymer length, e.g., high-molecular-weight HA (Mw > 1.8 × 10 6 Dalton) and low-molecular-weight HA, Mw 4–10 × 10 5 Dalton), The molecular weight of HA determines its activities. High-molecular weight HA inhibits mitogenic processes and possesses anti-inflammatory effects, whereas low-molecular weight-HA shows protumorigenic effects by enhancing proliferation and inflammation [ 58 ].…”
Section: Proteoglycansmentioning
confidence: 99%
See 1 more Smart Citation
“…HA turnover occurs in various molecular weights of HA distinguished by their polymer length, e.g., high-molecular-weight HA (Mw > 1.8 × 10 6 Dalton) and low-molecular-weight HA, Mw 4–10 × 10 5 Dalton), The molecular weight of HA determines its activities. High-molecular weight HA inhibits mitogenic processes and possesses anti-inflammatory effects, whereas low-molecular weight-HA shows protumorigenic effects by enhancing proliferation and inflammation [ 58 ].…”
Section: Proteoglycansmentioning
confidence: 99%
“…A few clinical trials are currently evaluating the therapeutic effects of combining hyaluronidase and chemotherapeutics ( Table 2 ). PEGPH20 showed clinical benefits with chemotherapy in PDAC in a phase 2 trial but did not show any clinical benefit in phase 3 trials [ 58 ].…”
Section: Therapeutical Targetsmentioning
confidence: 99%
“…9−11 In the case of CCA patients, researchers are gradually focusing on more targeted and safer drugs, as well as comprehensive treatment methods such as biological and gene therapies. 12 Metal−organic frameworks (MOFs) have been widely used in the field of drug delivery due to their ease of functionalization, tunable pore sizes, and flexible compositions. This is because MOFs can control particle size, surface chemistry, and internal porosity, enabling the design of complex materials based on MOFs.…”
Section: Introductionmentioning
confidence: 99%
“…for co-delivering two and three drugs with different anti-tumor mechanisms have exhibited great potential in the treatment of breast cancer. To improve active-targeting delivery, the vehicles were modified by different moieties, such as antibodies, polysaccharides, and various small-molecular ligands. Recent studies revealed that hyaluronic acid (HA) or chondroitin sulfate (CS) was used to modify nanosized carriers for tumor-targeting drug delivery by HA/CS-CD44 receptor-mediated endocytosis. Considering that CD44 receptors were highly expressed on breast cells, HA-modified vehicles could enhance drug internalization in the treatment of breast cancer …”
Section: Introductionmentioning
confidence: 99%